Uncovering effects of climate-sensitive health risks on historically marginalized youth in Washington State: creating opportunities for maximum involvement - Cassandra Jean; Amber S Khan; Graciela M Flores; Jamie Donatuto; Paulina Lopez; Crystal Perez; Carmen Martinez; Nicole A Errett (IOP Publishing, 2024)
Climate-sensitive hazards, including extreme heat, wildfire smoke, flooding, and rising sea levels, can jeopardize the health of all populations. However, certain population groups are more vulnerable to harm from these hazards. While youth-particularly those from historically marginalized groups and communities-are among those at the highest risk, their abilities may be underutilized in local climate adaptation efforts. This exploratory research aimed to identify opportunities for youth involvement in climate and environmental solutions in their historically marginalized communities. Specifically, this study (1) investigated youth risk perceptions and impacts of various climate-sensitive hazards (e.g. extreme heat, wildfire smoke, flooding, and sea level rise); (2) examined current barriers, resource needs, and opportunities for youth to engage in climate and environmental solution work; and (3) explored current methods and spaces where youth and community leaders can support youth-led climate-related initiatives. Through focus group discussions with youth and in-depth interviews with community leaders who are directly with youth, this study identified opportunities to leverage youth experiences, perceptions, and assets to promote a healthy and resilient community in the face of various compounding climate-related threats. Results showed that while youth recognize the changing climate and associated health impacts, they require more financial resources and support from local decision-makers to maintain their engagement and promote community resilience. Engaging youth in climate action and community resilience involves more than just centering youth voices and perspectives-it requires intentional collaboration, capacity-building, organizing, granting decision-making power, and other strategies to produce inclusive, intersectional, and sustainable solutions.